THE VOLCANOGENIC DEPOSITS OF NON-FERROUS METALS OF PALEOISLAND ARC ENVIRONMENT ASSOCIATED WITH WALL ROCK ALTERATIONS OF HOST ROCKS AND PROBLEMS OF ORE GENESIS (on the example of ore districts in Georgia, Armenia and Turkey) - Kekelia, S.; Kekelia, M.; Popkhadze, N.; Gagnidze, N. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The goal of our work is the study of ore wall rock zones of the volcanogenic deposits of non-ferrous metals of paleoisland arc environment (on the example of Madneuli ore deposit) and determination of the conditions of their formations using geochemical and geothermobarometrycal investigations. Methods: the mapping of the open pit of Madneuli deposit, determination of the content of trace elements by ICP-MS, in the US Geological Survey and Caucasian Institute of Mineral Resources chemical geothermobarometry investigations were held and the isotopic composition of oxygen and hydrogen in the ore was determined. The results:the structural features of ore deposits, character of ore wall rock zones were identified, mineral composition of metasomatic rocks was defined and the multistage formation of deposits was proved. Scientific novelty: at the end the conclusion (including some scientific ideas about the genesis of ore deposits) about genesis of volcanogenic deposits of Alpian paleoisland arc environment taking into account the studies of geothermobarometry investigations by the authors was given. Practical significance:described features of ore wall rock zones can be successfully used in other regions of the world in order to find new volcanogenic ore deposits.